DETERMINAN PREVALENSI STUNTING MENURUT PROVINSI DI INDONESIA - Asima Christina Pangaribuan; Made Dwi Setyadhi Mustika (Jurnal Ekonomi dan Bisnis, 2026)
Stunting is a condition of failure to thrive in children under five due to chronic malnutrition, resulting in lower height than their peers. This problem risks long-term impacts such as reduced intelligence, health problems, low productivity, and increased likelihood of living in poverty as adults. This study aims to analyze the effect of income per capita, economic inequality, government spending in the health sector, and access to proper sanitation on the prevalence of stunting in Indonesia, both simultaneously and partially. This study also examines the alignment between the factors that cause stunting and government policies. The study was conducted in 34 provinces with a total of 204 observations using the panel data regression analysis method. The results showed that together the four variables had a significant effect on stunting. Partially, income per capita, government expenditure in the health sector, and proper sanitation have a negative and significant effect on the prevalence of stunting. The economic inequality variable did not show a significant effect. Descriptive analysis shows the alignment between the factors causing stunting and the direction of government policy.